ERADICATION DEVELOPMENT OF CORRUPTION AND NEOLIBERALISM IN THE CURRENT ERA - Susila, Agna; Suharso, Suharso (Varia Justicia, 2018)
The practice of Corruption has been prevented and eradicated along with the development of the ideology of new liberalism (neoliberalism) which seems increasingly difficult to avoid and control. This study aims to analyze the evolution of eradicating Corruption and the development of unstoppable neoliberalism movement. This study uses normative methods (legal research) with short cases and conceptual approaches. The two issues above are a big problem in our country because no matter how strong the prevention and eradication efforts are carried out, it turns out case by case that proves the existence of acute "immunity" from these two diseases, so it needs an "effective" therapy to deal with it. Pancasila became one antidote to inhibit the breeding of two of the above diseases. Like cancer cells, the family is the primary key to the goal of preventing the spread of this disease. Therefore, efforts to isolate the family from the contamination of the two conditions above are an essential solution.